2001
DOI: 10.1002/j.0022-0337.2001.65.10.tb03448.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Metal Ions and Susceptibility to Dental Caries

Abstract: Results from several epidemiologic studies have shown that there are large differences in the prevalence of dental caries from one region to another within the United States as well as in other countries. It has been postulated that the observed differences may be attributed in part at least to exposure to trace elements such as selenium, vanadium, molybdenum, strontium, and lead. Although data from epidemiologic studies usually support this hypothesis, direct evidence is sparse with the possible exception of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…Higher Pb level in urban drinking water (0.0098 + 0.0005 ppm) than wells drin-king water (which is not detected) with hi-gh significant differences in the value of dmfs in the urban area (20.24 + 10.74 ppm) than rural area (7.92 + 5.28 ppm) (p<0.001). These indicated toward the cari-ogenic role of Pb which agreed with Bowen (29) who found a strong positive correlation between caries prevalence and concentration of Pb in drinking water.…”
Section: -------------------Sd: Standard Deviationsupporting
confidence: 88%
“…Higher Pb level in urban drinking water (0.0098 + 0.0005 ppm) than wells drin-king water (which is not detected) with hi-gh significant differences in the value of dmfs in the urban area (20.24 + 10.74 ppm) than rural area (7.92 + 5.28 ppm) (p<0.001). These indicated toward the cari-ogenic role of Pb which agreed with Bowen (29) who found a strong positive correlation between caries prevalence and concentration of Pb in drinking water.…”
Section: -------------------Sd: Standard Deviationsupporting
confidence: 88%
“…When strontium and fluoride were copresent, an increase in crystallinity of carbonated apatites, a surrogate for dental enamel, was noted (Featherstone, Shields, Khademazad, & Oldershaw, 1983). Similar effects were proposed for theobromine (Nakamoto, Simmons, & Falster, 1999& 2001. Hence, the present laboratory study was concerned with investigating potential additive or synergistic anti-caries effects between fluoride, strontium, theobromine and their combinations.…”
Section: Introductionmentioning
confidence: 58%
“…Theobromine has been shown to enhance crystallinity of apatites without affecting remineralization in animal caries studies (Nakamoto, Simmons, & Falster, 1999& 2001 although no hypothesis on its mode of action has been provided yet. Theobromine (primarily found in cocoa and cocoa products) belongs to the group of methylated xanthines and is structurally similar to caffeine (coffee, tea) and theophylline (tea, cocoa), two other naturally occurring alkaloids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They enhances uptake and retention of fluorides applied topically and also shows antibacterial effect against cariogenic microorganisms. 44 Trace elements promoting caries formation are Selenium, Zinc, Manganese, Copper, Barium, Lead, Calcium, Cadmium, Arsenic, Iron, Potassium and Zirconium. 44 Studies done by Glass RL et al, 45 Anderson RJ, 46 Schamschula RG et al, 47 Glena R et al, 48 Gauba K et al, 49 Bowen WH 44 concluded that Selenium, Copper, Iron, Manganese, Lead, Zinc showed positive association with caries while Fluoride, Calcium, Magnesium, Molybdenum, Vanadium, Strontium, Lithium were associated negatively with caries experience.…”
Section: Role Of Other Trace Elements On Dental Cariesmentioning
confidence: 99%